Triadic Framework of Sharīʿah Law: A Systematic Review of Al-Ḥākim, Al-Maḥkūm ʿalayh, and Al-Maḥkūm Fīh - M. Lutfi Khakim; Siti Nurjanah; Warsono Warsono; Taufid Hidayat Nazar (Journal of Social Science and Humanities, 2026)
Contemporary studies in Islamic jurisprudence (Hukm Shar'ī) have expanded considerably in response to the growing complexity of issues in the social, economic, institutional, environmental, familial, and digital religious authority domains. Existing literature, however, tends to center its analytical focus on Al-Ḥākim — the divine legislating authority — through discussions of legal proofs (dalīl), the objectives of Islamic law (maqāṣid al-sharī'ah), independent legal reasoning (ijtihād), analogical deduction (qiyās), legal causation (ta'līl), and methods of legal determination. By contrast, the dimensions of Maḥkūm 'Alayh (the legally obligated subject) and Maḥkūm Fīh (the object of legal prescription) remain largely underexamined at the operational level. This article aims to map prevailing trends in contemporary research on Hukm Shar'ī and to develop a conceptual synthesis grounded in the triadic relational framework among Al-Ḥākim, Maḥkūm 'Alayh, and Maḥkūm Fīh. The study employs a systematic literature review methodology with narrative-thematic synthesis, drawing on 68 core articles selected from an initial pool of 321 records retrieved through Scopus metadata-based screening. The review findings indicate that the literature is predominantly oriented toward istiṇbāṭ (legal inference) methodology and maqāṣid-based inquiry, while thematic areas such as bioethics, criminal law (jināyah), worship-related services, family law, and collective action remain comparatively underdeveloped. The principal findings identify conceptual, methodological, applicative, and subject-level gaps — most notably, the insufficient analytical treatment of legal capacity, agency, vulnerability, the obligations of the mukallaf (legally competent subject), and the juridical status of institutional acts. This article concludes that the triadic framework of Hukm Shar'ī has significant potential to reinforce the theory of ḥukm and to serve as an analytical instrument for engaging with contemporary issues in Islamic law in a more systematic, contextual, and responsive manner.